Out of Africa: The genomic footprints of Vietnamese Robusta coffee. - Tram Vi; Thi Nhu Le; Philippe Cubry; Viet Ha Phan; Thi Tieu Oanh Dinh; Thi Bich Ngoc Tran; Van Toan Nguyen; Claude Patrick Millet; Jean-Léon Kambale; Gba Kossia Manzan Karine; Pascal Musoli; Ucu Sumirat; et al. (PLoS ONE)
Vietnam is the main producer of Robusta (Coffea canephora) coffee, but faces several future agronomic challenges. These may be addressed through breeding for improved cultivars and more sustainable cropping systems. For such efforts to be successful and efficient, locally available genetic resources must be understood. Indeed, while C. canephora exhibits high genetic diversity in its native tropical African forests, only a part of it contributed to the worldwide diffusion of Robusta. Here we traced the African origins of Robusta accessions cultivated in the Central Highlands of Vietnam. A total of 126 Robusta accessions from the Vietnam coffee germplasm collection were characterized, including historical, elite and local cultivated clones. Their genetic diversity and origins were inferred through comparisons with wild reference samples using a new set of 261 genome-wide SNPs. A core set of 45 accessions that maximize the genetic distance and allelic richness were identified for conservation and breeding priorities. Full genome sequencing of these individuals helped to closely trace the origins of chromosomal segments back to different, geographically-structured wild African genetic groups. All Vietnamese Robusta accessions displayed Congo Basin (ER group) origins, albeit to various extents. However, we also uncovered contribution from several other genetic groups, variously from the Guinean region (D), the central African Atlantic coast (AG), and Eastern CAR/Uganda (OB), in 31 hybrid individuals. These source groups have been widely used in crossbreeding to develop elite clones. In addition, using whole-genome sequencing data, we also identified various admixture patterns at the chromosome level among the hybrids, which might provide valuable information for selecting breeding materials.